Towards a monophyletic classification of Lejeuneaceae III: the systematic position of Leiolejeunea - Schäfer-Verwimp, Alfons; Feldberg, Kathrin; Dong, Shanshan; van Melick, Huub; Peralta, Denilson F.; Schmidt, Alexander R.; Schneider, Harald; Heinrichs, Jochen (Phytotaxa, 2014)
The derived liverwort Leiolejeunea grandiflora was recollected at the type locality in Jamaica after more than 100 years. The characteristics of its oil bodies were described for the first time based on the new collections. Each leaf cell possesses 2-4(-6) rather small, subhomogeneous to very finely segmented, subglobose to ellipsoidal, colorless oil bodies. The plants were either dioicous or autoicous. DNA sequences of two chloroplast regions (trnL-trnF, rbcL) and the nuclear ribosomal ITS region were obtained for two accessions of Leiolejeunea to enable the inference of the phylogenetic relationships of these plants. Based on Bayesian inference of phylogeny as well as maximum parsimony and maximum likelihood analyses of a dataset including 87 representatives of Lejeuneaceae, Leiolejeunea was found as the putative sister to either Echinolejeuneinae or Cheilolejeuneinae. Thus, we propose the new monogeneric subtribe Leiolejeuneinae with relationships to Cheilolejeuneinae and Echinolejeuneinae. The analyses included also one accession of the generitype of Cheilolejeunea, C. decidua [= Cheilolejeunea adnata]. This species was found in a well supported sister relationship with Cystolejeunea. To avoid nomenclatural confusion, we propose a wide genus concept for Cheilolejeunea including Aureolejeunea, Cyrtolejeunea, Cystolejeunea, Evansiolejeunea, Leucolejeunea, and Omphalanthus.